(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
With 48 years of experience working at Teatro Amazonas, Mr. Raimundo Nonato reports, in this interview, his trajectory of work and technical learning with the stage crew of one of the most renowned theaters in Brazil. His daily practical experiences, full dedication to the functions performed and a great love for the workspace led him to receive numerous decorations, honors and interviews coming not from his state, Amazonas, but also beyond Brazilian borders with international recognition.